Assessment in the form of met-ocean events of the wave climate in West Africa - (:unkn) unknown (My University, 2015)
Accurate estimation of long-term sea conditions is a major issue in design of coastal and offshore structures, coastal zone management or wave energy harvesting. An estimation of long-term sea conditions requires long duration observational data while in West Africa, only a few (3 years) years of observational data are available. To overcome the limits in duration that observations impose, a stochastic approach, event-based representation of sea state data, is proposed to model the wave climate in West Africa. An “event” refers to a wave system (swell or wind sea) evolving over time, that can be observed for a finite, yet significant duration and that can be linked to a single meteorological source phenomenon (e.g. low pressure systems, storms, etc.). Event-based approach provides structures with physical meaning and temporal consistence for the representation of sea states data. The procedure we have used is decomposed into three following steps. First, we have extracted events from a time series of directional spectra. We have then developed a model to represent each event by a reduced number of parameters. In the last step, we have constructed the stochastic events generator which allows for simulation of individual events and for reconstruction of wave climate over durations of arbitrary lengths. Results showed good agreement between reconstructed climate and that of reference and allow to conclude that the stochastic events generator can reliably be used to simulate sea state data in West Africa for a ocean engineering applications.
Keywords: African Research